2011
DOI: 10.1007/s10549-011-1791-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication of breast cancer recurrence risk

Abstract: Purpose Doctors commonly use genomic testing for breast cancer recurrence risk. We sought to assess whether the standard genomic report provided to doctors is a good approach for communicating results to patients. Methods During 2009–2010, we interviewed 133 patients with stages I or II, node-negative, hormone-receptor positive breast cancer and eligible for the Oncotype DX genomic test. In a randomized experiment, patients viewed 6 vignettes that presented hypothetical recurrence risk test results. Each vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 37 publications
1
73
1
1
Order By: Relevance
“…42 A recent survey found an increase in the use of testing from 14.7% in 2006 to 27.5% in 2008 (P < 0.01), 3 and current rates of use are likely to be higher. Nevertheless, there are indications that eligible African-American women may be tested at rates lower than white women; 3 further investigation of this finding will be critical if the test is demonstrated to have clinical utility.…”
Section: Contextual Issues Important To the Recommendationmentioning
confidence: 99%
See 3 more Smart Citations
“…42 A recent survey found an increase in the use of testing from 14.7% in 2006 to 27.5% in 2008 (P < 0.01), 3 and current rates of use are likely to be higher. Nevertheless, there are indications that eligible African-American women may be tested at rates lower than white women; 3 further investigation of this finding will be critical if the test is demonstrated to have clinical utility.…”
Section: Contextual Issues Important To the Recommendationmentioning
confidence: 99%
“…Studies have begun to document how medical and surgical oncologists use the test, how they communicate results to patients, how well patients understand the information, and how they use it in decision making. [42][43][44][45] Although studies to date are too small to allow firm conclusions, their findings indicated that physicians generally assume the test has clinical utility and many use it as a primary tool in discussing risks and benefits of chemotherapy with women who have HR+ early breast cancer, often by directly sharing with them the report provided by Genomic Health. 42,44 Explanation and discussion of intermediate risk are very challenging, and decisions are ultimately made by incorporating consideration of other clinical factors as well as patients' views and preferences.…”
Section: Contextual Issues Important To the Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching precise information can be less effective because people can get all the details right but still fail to comprehend the actual gist meaning that would lead to more informed decisions. Standard, detailed medical reports about risk of breast cancer do not adequately convey the important decision relevant information about the meaning of risk to patients, whereas less complex, gist-based reports can more effectively convey such information, suggesting that facilitating appropriate gist representations of information is more useful in the context of understanding risk of breast cancer (Brewer, Richman, DeFrank, Reyna, & Carey, 2012). Additionally, we have found that a preference for integrating qualitative gist information and quantitative base rates assessed by the fuzzy processing preference index ) predicts accuracy at estimating a woman's degree of genetic breast cancer risk .…”
Section: Gist Explanationmentioning
confidence: 99%